SEGMENTASI WISATAWAN TAMAN AGROWISATA TENAYAN RAYA KOTA PEKANBARU PROVINSI RIAU - Ihsan, M. Ikhwanul; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Garden agro tours Tenayan Raya Pekanbaru city, it is one of the attractions that deserve to be developed, because the number of visits from year to year continues to increase. The reason the researchers chose the agro- tourism of pekanbaru city of riau province is the first agro tourism area in pekanbaru city and the agro- tourism park is quite interesting, which combines farming areas, farms and game riders into a beautiful area. This study aims to describe the segmentation of tourists in Taman Agro Tourism Tenayan Raya Pekanbaru City Riau Province. The method used in this research is quantitative descriptive method. From the result of the research, it is known that the geographical segmentation of 86% comes from the city of Pekanbaru and 14% from outside Pekanbaru, female demographic segmentation is 67% and males 33%, age 26- 35 years 39% , 83% are married and 17% are unmarried, then on average have 4 core family members, 59% senior high school education, with an average job as an entrepreneur of 40% with monthly expenses of Rp. 3,000,000-4,000,000. Then psychologically tourists who come to visit the Agro Park Tenayan Raya Tour Pekanbaru city on average with families, tourists who come more happy to use a motorcycle. The average tourist knowing information about Taman Agro Wisata Tenayan Raya Pekanbaru City comes from relatives of 81% and is willing to recommend the location to others by 93%. Tourists who come to visit with the aim to relax by 46%. Tourists who use restaurant and gazebo facilities as many as 100 people, fruit garden as many as 60 people, mini market as many as 40 people, fishing ponds, 37 people, toilets as many as 30 people and outbound arena, outfit, rice fields, vegetable garden 29 people sebalamak. While the tourists who are interested in doing activities such as, taking 88 people, 60 people harvest, 37 people fishing, 29 agro-educational and outbound activities, 18 archery, flying fox as many as 11 people and family gathering as many as 6 people . Keywords: Segmentation, Tourist, Agro Tourism.